Déficit de atención y desarrollo cognitivo en los estudiantes de la escuela fiscal “Once de Noviembre”, Riobamba, 2016 - Paredes Oleas, Priscila Mishel (2018)
The objective of this research was to determine the relationship of the attention deficit in the cognitive development of the fourth year students “C” of the Fiscal School “Once de Noviembre” of the city of Riobamba, province of Chimborazo in the period February 2016 – August 2016 the same one that was based on the problematic that has been evidenced in the students the difficulties that have been affecting their cognitive development, after analyzing the environment of the problem that affects them, theoretically the work was based on the variable independent is the Attention Deficit and the dependent Cognitive Development, methodologically the design is non-experimental, field, by the level is diagnostic-correlational, the scientific method was applied through the Deductive-Inductive process, the population with the one that was worked was of 29 students of fourth year parallel “C” of the Fiscal School “Once de Noviembre”, “the sample was not probabilistic because its sampling was random and intentional, the technique used for the independent variable was Test D2, the same one that evaluated, for the dependent the Wisc-R test was used, same that measures the intellectual abilities of students, so study could reach the conclusion that the attention deficit if it affects students so study could reach the conclusion that the attention deficit if it affects students the same as it was reflected in their performance.